The Pre- 3 b. y. Crust:: Fact-Fiction-Fantasy - Bridgwater, D.; Fyfe, W. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1974)
Summary At this time the oldest rocks on Earth occur in W. Greenland. Radioactive dating methods give ages of about 3.8 billion years. The rock types involved are a complex mixture of metasediments, metavolcanic and intrusive rocks. The rock types appear to be rather normal in terms of modern analogues. But the structural geology of this, and similar ancient regions, indicates that ancient tectonic patterns may be unique. It is suggested that differentiation of the Earth was advanced 4 billion years ago and that there was an extensive acid crust.